Recent advancement in the anticancer efficacy of the natural flavonoid scutellarin: a comprehensive review - Elsori, Deena; Pandey, Pratibha; Verma, Meenakshi; Vadia, Nasir; Roopashree, R.; Vyas, Manish; Lakshmi, L.; Maharana, Laxmidhar; Nathiya, Deepak; Saeed, Mohd; Obaidur Rab, Safia; Khan, Fahad (Frontiers in Pharmacology, 2025)
Scutellarin (SC), a natural flavonoid, has been expansively employed in treating innumerable inflammation-related diseases due to its antitumor, antiinflammatory, anticancer, and antioxidant potential. Scutellarin can inhibit significant inflammatory cell signaling pathways, comprisingPI3K/Akt, NF-κB, and MAPK, and while activating antioxidant-related pathways such as Nrf2 and ARE. Numerous reviews have outlined scutellarin’s pharmacological effects and associated mechanisms in inflammation-related diseases. Several studies have elucidated the mechanisms of anticancer activity by inhibiting various signaling pathways; however, to our knowledge, none of the reviews have distinguished the anticancer potential of scutellarin based on different human cancer types. Our review outlined detailed insights about the anticancer potential of scutellarin based on cancer type in the human body. Furthermore, we have also outlined formulations, combinatorial therapies, and comprehensive mechanistic research to deliver enhanced and effective treatment options for cancer patients. This study will provide thorough and detailed insights into scutellarin, supporting its development as a promising candidate for cancer treatment.